The effect of online learning and proscrastination behaviour on well-being among Undergraduates in Universiti Malaysia Sabah - Choo, Ming Hui; Norzihan Ayub (2021)
In 2019, the global economy was hit by an unexpected coronavirus outbreak. Hence, people are encouraged to practice social and physical distancing, which, in turn, means all the education sectors are forced to close down and be replaced by online learning. Furthermore, students' procrastination is common nowadays, especially in this pandemic, and the well-being of undergraduates is now being addressed globally, as undergraduates will be the pillars of the future. Previous research has discovered a negative relationship and a negative impact on students' well-being between online learning and procrastination behaviours. Students’ mental and physical health do not improve significantly during distance learning due to the lack of social interaction with peers and excessive usage of online learning technologies, in addition to students’ procrastination. When students procrastinate, they will feel better momentarily. However, it will certainly bring tension and anxiety to one’s life in the long term, thus causing students to experience poor well-being. However, procrastination was found to be linked with online learning and this adversely impacted students’ well-being.